KEPEMIMPINAN SEBAGAI PRIVILEGE: KRITIK TERHADAP TEORI SIFAT DALAM MEMBENTUK BIAS KEPEMIMPINAN - Irma Yusnia; Hasna Mutia Insani; Virda Andhara Sofia; Nurul Widya Tanjung; Fathur Rokhman; Nina Oktarina; Gunawan Tjokro (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
One of the fundamental aspects of an organization is the success of leadership. Reality shows that leadership is not solely determined by innate traits, but also by social context, experience, and interaction with the environment. Therefore, a critical review is needed to reassess the relevance of trait theory in the context of contemporary leadership. This study is a descriptive study that employs a literature review method using data sources such as books, journals, and documents relevant to the topic. The findings indicate that trait theory in leadership positions individual characteristics as the primary factor in a leader’s effectiveness; the existence of normative standards regarding the ideal leader is linked to specific social contexts; there is a connection between trait-based approaches and limited access to leadership positions; and there is a shift away from focusing exclusively on individual traits. Furthermore, a leader’s focus on privilege can reinforce inequality and hinder the creation of inclusive and equitable leadership.